Enhancing English Reading Proficiency through Student Reading Habits - Nurul Lailatul Khusniyah (AL-ISHLAH: Jurnal Pendidikan, 2024)
This research aims to obtain students' reading habits to strengthen their English reading skills. This research uses a desciptive qualitative approach. This research examines phenomena related to students' reading habits in strengthening and improving English reading skills. The sample was 100 fifth-semester students of the English Reading Class. The sampling technique uses purposive sampling. The data collection process uses three types of data: 1) observations obtained to observe students' reading habits during learning activities and 2) questionnaires given to students to find out their habits outside the classroom according to their point of view and the situations they experience. The data analysis technique uses three stages, namely data reduction, data presentation, and conclusion. The results of this research conclude that students have good reading habits in the campus environment and read a lot of books to complete their coursework. Meanwhile, reading activity at home is very low and parental support in building reading habits is also non-existent because reading activities together are not carried out at home. The results of this research also have implications for teachers' understanding of how to motivate students to have high reading habits outside the classroom and also provide authentic teaching materials so that reading activities can be done more outside the classroom.